Polyoxometalate‐Enhanced 3D‐Printed Supercapacitors. Issue 23 (4th November 2022) - Palacios‐Corella, Mario; Ghosh, Kalyan; Redondo, Edurne; Pumera, Martin
Abstract: The contemporary critical energy crisis demands the fast and cost‐effective preparation of supercapacitors to replace old‐fashioned batteries. 3D‐printing has been established as a fast, cheap, and reliable new manufacturing technique that enables the preparation of such devices.. Unfortunately, carbon‐based filaments used in 3D printing lack the necessary electrical properties to build supercapacitors by themselves and have to be combined with other materials to reach their full potential. In this study, carbon‐based 3D‐printed carbon electrodes (3D‐PCE) have been combined with two polyoxometalates (that share the same redox cluster) by drop casting of the inorganic cluster mixed with a conducting slurry. The modified electrodes show higher capacitances than reference carbon electrodes showing the exceptional properties of the polyoxometalates. Moreover, the different nature of the polyoxometalate counter ions allows for their distinct deposition, giving rise to a different coverage of the surface of the 3D‐PCE. The different coverage and the nature of the interaction of the counter ion with the electrolyte significantly modify the capacitance and resistance of the materials, playing a key role that should not be overlooked during their preparation. Abstract : Printer wonderland : 3D‐printed carbon‐based electrodes are modified with two [V10 O28 ] 6− polyoxometalates with different solubilities. The modified electrodes display better electrochemical properties than reference carbon electrodes, showing the exceptional properties of the polyoxometalates and allowing for the preparation of polyoxometalate‐enhanced 3D‐printed supercapacitors.